Is There A Role For Earnings Management in Dividend Policy? - Alwan Sri Kustono; Rendy Mirwan Aspirandi; Bryan Chandra Varisa (Juara: Jurnal Riset Akuntansi, 2021)
The study examines whether the dividend policy is affected by managerial ownership, free cash flow, or earnings management and the role of earnings management, such as mediating variables. Five hypotheses were tested with path analysis. Testing uses SmartPLS version 3.2.9. The population was the manufacturing companies in 2014-2018. The research period is limited to 2018 to avoid Covid 19 impact. There are 125 year-firms observations used to confirm the hypotheses. The result shows managerial ownership and free cashflows affect dividend policy and earnings management. Earnings management is not a mediating variable. This result rejects the previous research results, which concluded that earnings management influences dividend policy. The implication is earnings management is not a good explanation to see changes in dividend policy. Earnings management is challenging to plan dividend policy. Further researchers need to pay attention to the measurement of various types of earnings management that are more precise in management policies.